Renewable Energy, GDP (Gross Domestic Product), FDI (Foreign Direct Investment) and CO2 Emissions in Southeast Asia Countries - Mai, Tran Ngoc (International Journal of Energy Economics and Policy, 2023)
The increasing rate of economic growth and globalization of the global economy has raised concerns regarding sustainable development, and renewable energy is being explored as a possible solution. The interrelationship between economics, environment, and energy consumption has been widely researched amongst academics worldwide; however, due to the inconsistent results, further exploration is needed to clarify the matter. Thus, this study seeks to investigate potential factors such as foreign direct investment (FDI), gross domestic product (GDP), and carbon dioxide (CO2) emissions that impact renewable energy consumption in countries within Southeast Asia. This research suggests that FDI flows bring positive aspects to the region's renewable energy sector while GDP and CO2 emissions have negative impacts. These findings can thus be employed as baseline information for future policies that strive to expand renewable energy activities in the region.